2019
DOI: 10.1097/icb.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Melanoma, Sector Melanocytosis, and Retinal Pigment Epithelial Microdetachments in Birt–hogg–dubé Syndrome

Abstract: The BHDS can be associated with tumors of the skin and kidney. In this case, we noted ocular melanocytosis, malignant choroidal melanoma, and bilateral pinpoint retinal pigment epithelial detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some data suggest that BHD patients might have an increased risk of melanoma, but this remains controversial. There are case reports of both malignant skin [99][100][101][102] and choroidal melanoma [103,104], which may be familial [102,105] and/or multiple [102,105], and even more debated reports of multiple atypical nevi [102]. One small study found a risk of melanoma in confirmed BHD as high as 10%, which is much higher than the 1.8-2.4% risk in the general population [105].…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Some data suggest that BHD patients might have an increased risk of melanoma, but this remains controversial. There are case reports of both malignant skin [99][100][101][102] and choroidal melanoma [103,104], which may be familial [102,105] and/or multiple [102,105], and even more debated reports of multiple atypical nevi [102]. One small study found a risk of melanoma in confirmed BHD as high as 10%, which is much higher than the 1.8-2.4% risk in the general population [105].…”
Section: Cutaneous Manifestationsmentioning
confidence: 99%
“…Although BHDS has a well-known link with malignancy, especially renal cancer, it is infrequently considered in dermatology patients with atypical nevi and melanoma 2 . However, increased melanoma risk, including choroidal melanoma, is associated with BHDS 3, 4, 5, 6, 7, 8, 9. Here, we report a patient with multiple primary cutaneous melanomas and atypical nevi that triggered evaluation for an underlying genetic cause.…”
Section: Introductionmentioning
confidence: 92%
“…Pathogenic germline variants in other genes, such as MBD4 , have been reported in UM patients in relation to the predisposition to develop such tumors [ 16 , 17 , 18 ]. Additionally, certain case reports have linked UM development to germline mutations in genes like CDKN2A , BRCA1/BRCA2 , MLH1 , MSH6 , FLCN , and POT1 [ 19 , 20 , 21 , 22 , 23 , 24 ]. Recent findings suggest moderate evidence of hereditary predisposition to UM through germline mutations in MLH1 or PALB2 , indicating locus heterogeneity for UM predisposition [ 25 ].…”
Section: Introductionmentioning
confidence: 99%